Fuzzy model for evaluation of selected Diabetes Medical Sites - Abed, Majida Ali; Alasadi, Hamid Ali Abed (IJRDO -Journal of Computer Science Engineering, 2016)
The aim of this paper is to give model to evaluate Diabetes Medical Sites (DMSs) quality by fuzzy system to arrange these sites according to their quality depending on the values that get it during the application of the model on these sites. This model contain the most important element suggested for quality criteria like the Design Site, Update Site, Hyperlinks, Ability of User, Insufficient, Information, Use of visual effects, Data on the sources, time Input, Consistency content with goals of site. The particular goals of this work were to identify criteria for the evaluation of DMSs such as legitimacy; dependability, and usefulness and find out the weakness of those sites. The particular goals of this work were to identify criteria for the evaluation of DMSs, reconnoiter; usability of recognize criteria for the evaluation of DMSs with the identified criteria for the corroboration; of legitimacy; dependability, and usefulness; and find out the weakness of those sites. Additional, we give propositions; for improving the usability, content quality, dependability, performances and some other elements that must took care when evaluating sites and documentation information can use it in scientific research.